Pengaruh Fitur Shopping Live Terhadap Pembelian Impulsif Pengguna Aplikasi Shopee. - Rahma Dini Aulia; Najwa Khoerunissa; Abdul Yusuf (Economic Reviews Journal, 2024)
The aim of this study is to investigate whether shopping live features influence impulse buying. A total of 100 respondents who met the requirements were collected as a sample based on research conducted using a questionnaire. Confirmatory factor analysis and Cronbach Alpha were used to evaluate the validity and reliability of respondents' responses to statement items. Simple regression analysis was used to assess the research hypothesis. Based on these experiments, this research determines that the live shopping feature has an impact on impulse purchases made on the Shopee platform.